CYST NASOLABIAL FOLDS - Lepsky, V.V. (World of Medicine and Biology, 2015)
Introduction. Nasolabial cyst - a congenital neoplasm tumor, localized in the soft tissues of the upper projection ruin in canine and lateral incisor. The cause of the nasolabial fold cysts are considered two theories. According to one, get more distribution, the cyst is formed from the remnants of the epithelial tissue remaining after the merger in the embryonic period of the lateral nasal, maxillary and globular processes [1, 2, 3]. According to the second theory, proposed later nasolabial cyst is formed from the nasolacrimal duct. Proliferation and cystic degeneration of the remnants of fetal tissue usually begins after age 30, even if these remains are preserved from birth. Cyst nasolabial folds more often seen in women, has the form of soft tissue formation, located under the upper lip, which can be shifted up wing of the nose, lead to the expansion of the nasal passage and the deformation of the nasolabial fold. Depending on the size of the cyst can be hard or soft to palpation, difficult wearing dentures in the upper jaw. If you puncture the cyst was light yellow or straw-yellow liquid. The cyst is usually one-sided and not soldered to the underlying bone, resulting in the continued viability of the upper jaw. Sometimes the pressure on the bone cyst is a local deformation of it. Treatment of these cysts surgery [1, 2, 4, 5]. Most textbooks in the description section of benign tumors and tumor-like growths cyst nasolabial folds referred to in the classification, given that it relates to neodontogennym cysts, but the description of the source of growth, its causes, clinical course and treatment methods have been found. Obviously, therefore, dentists are not familiar with this pathology. Therefore, our purpose was to familiarize physicians with the development and clinical manifestation of tumors and treatment. Objects and methods of research. A clinical study and treatment of patients 47-years, appealed to the surgical department of our clinic. Results of the study. Patient 47-years complained of the presence of asymmetry of the face due to swelling of the upper jaw on the left wing in the area of the nose, painless. From the history of the disease found that swelling noticed about two years ago, at first did not address to the doctor when the swelling has increased in size and there was a marked asymmetry of the face, I turned to vrachu Otorhinolaryngological. The doctor has diagnosed - the boil and appointed physiotherapy №10 (UHF). After the adoption of the assigned treatment the patient’s condition did not improve and she decided to seek help from a doctor dentist. When viewed in the surgical department of our clinic, the patient revealed asymmetry of the face due to swelling of the tissues of the upper lip to the left, slightly raised nose wing. Skin color is not changed. Lymph nodes are not palpable. Palpable tumor is defined by the left upper lip tightly-elastic consistency, not soldered to the skin, painless, tightly adherent to the bone. When viewed from the left nasal passage on the bottom surface of the protrusion found rounded, covered with thinning of the mucosa, soldered to the bottom of the nose. Opening the mouth free, mucosa of the vestibule of the oral cavity in color is not changed, the teeth of the upper jaw from 2.2 to 2.5 - intact, their percussion painless temperature reaction negative. Gums pale pink. On the alveolar bone protrusion found coming from the transitional fold to 2.2 and 2.3 crowns of teeth, not covered with mucosal changes, the size of a length up to 3 cm wide and 2 cm, was found floating palpation painless. We had been diagnosed with a cyst of the left nasolabial fold. The patient asked to surgery, to which she agreed. The operation was performed under local anesthesia, infiltration anesthesia made on a transitional fold in 2.2, 2.3 teeth 2% lidocaine - 3.0 mm s application anesthesia 10% lidocaine mucosa of the left nasal passage. He made the cut on a transitional fold from 2.1 to 2.4 teeth, loose mucosa to cystic formation. The cyst was bluntly detached from the alveolar bone, found in the upper cord cysts, leading to the lower nasal passage. Strand of separated bluntly, the bottom portion of the mucous membrane of the nose with tyazham excised, the cyst is removed, the wound sutured with catgut the bottom of the nose tightly. On the alveolar bone deformation is detected, it is obvious from the pressure of the cyst. The flap is laid back into place. The wound on the transitional fold sutured with catgut. The postoperative period was uneventful. When dressings performs processing seams in the oral cavity and in the lower nasal passage. Wounds zazhilipervichnym tension. Histologically found epithelial cells, unstructured substance, blood cells, hence diagnosis cysts confirmed. But, given the discovery of the cystic cavity in the bottom of the nasal passage, in our opinion, it could be a retention cyst mucous glands of the nose bottom, lowered to the nasolabial fold due to prolonged growth and the accumulation of content in the cystic cavity.